1997
DOI: 10.1002/(sici)1099-0798(199722/06)15:3<329::aid-bsl276>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

The MacArthur adjudicative competence study: diagnosis, psychopathology, and competence-related abilities

Abstract: A set of measures assessing abilities related to legal standards for competence in the adjudicative process were administered to mentally‐disordered criminal defendants with diagnoses of schizophrenia, affective disorder, other psychiatric disorders, and to criminal defendants without diagnosed mental disorder. Mentally‐disordered defendants were recruited from two groups: those who had been committed for restoration of competence and those who had been identified by jail personnel as mentally ill. Significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 5 publications
0
7
1
1
Order By: Relevance
“…In addition to the dearth of literature describing the effects of personality disorder on decision‐making capacity, the measures used to determine capacity have not been validated for patients with primary personality disorder diagnoses. This includes the MacArthur Structured Assessment of Competencies of Criminal Defendants (MacSAC‐CD), which was validated for schizophrenia and affective disorders , and the MacCAT‐T, which was validated for schizophrenia and schizoaffective disorder . Similarly, up to this point impairment in executive function seems to be the most significant cognitive predictor of inability to obtain the standards required to maintain independence in decision‐making .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the dearth of literature describing the effects of personality disorder on decision‐making capacity, the measures used to determine capacity have not been validated for patients with primary personality disorder diagnoses. This includes the MacArthur Structured Assessment of Competencies of Criminal Defendants (MacSAC‐CD), which was validated for schizophrenia and affective disorders , and the MacCAT‐T, which was validated for schizophrenia and schizoaffective disorder . Similarly, up to this point impairment in executive function seems to be the most significant cognitive predictor of inability to obtain the standards required to maintain independence in decision‐making .…”
Section: Discussionmentioning
confidence: 99%
“…However, when in crisis they can find it difficult to withstand short term destructive “solutions” to their inner discomfort (Linehan 1993 ). Accordingly, they are in many ways similar to addiction patients, for whom Ulysses contracts have been discussed since long: they are generally considered to be decision competent (in a standard meaning of the term—see more below) (Hoge et al 1997 ; Applebaum and Grisso 1995), but have difficulties resisting impulses or cravings to use potentially dangerous substances. In this article, however, we will not scrutinize the arguments concerning Ulysses contracts for patients with other psychiatric disorders than BPD, and we do not take a stand on whether the use of Ulysses contracts is justified for patients with other diagnoses.…”
Section: Ulysses Contracts In the Treatment Of Patients With Bpdmentioning
confidence: 99%
“…When it comes to decision competence and psychiatric disorders, the MacArthur Treatment Competency Study in the 1990s found that the majority of patients with schizophrenia and depression were decision competent concerning psychiatric and medical treatment (Hoge et al 1997 ). The study also found that decision incompetence was correlated to disorganized thought processes rather than delusions or hallucinations alone (Hoge et al 1997 ; Applebaum and Grisso 1995 ). Thus, severe mental illness by itself does not prove the patient decision incompetent in matters of psychiatric treatment.…”
Section: Arguments Supporting the Use Of Legally Binding Ulysses Contmentioning
confidence: 99%
“…zdolność odniesienia się do nich, przedstawienia lub nie dowodów na swoją korzyść, • jaka jest jego odporność na nowe informacje w czasie postępowania (także niekorzystne), • czy posiada zdolność do zapamiętywania (notowania) przebiegu rozprawy, • jak postrzega obrońcę i jakie ma wobec niego oczekiwania, • czy potrafi wydawać adekwatne instrukcje prawnikowi co do prowadzenia obrony, • jaka była jakość jego relacji z poprzednimi prawnikami, • czy jego stan psychiczny stanowi realne zagrożenie dla życia lub zdrowia mimo możliwych do stosowania oddziaływań medycznych (ryzyko dokonania samobójstwa, samouszkodzeń, aktów agresji, kontrola zachowań impulsywnych) [2,13,[24][25][26]. Należy rozróżnić dwa możliwe stany oskarżone-go, tj.…”
Section: Specificity Of Researchunclassified
“…[2,13,[24][25][26]. Two different states of a defendant should be differentiated-incompetency to stand trial demonstrating itself through obviously wrong decisions from the defendant's ignorance, which of course does not result from a disturbed mental state [13].…”
Section: Specificity Of Researchmentioning
confidence: 99%